Vojtov V.A., Bekirov A.SH. Mathematical model of transition processes in tribosystems and results of modeling. - Войтов, В. А.; Бекиров, А. Ш. (Problems of Tribology, 2018)
A mathematical model of the dynamics of the transient processes of the wear rate and the coefficient of friction in tribosystems is developed. The equations of the dynamics of transient processes in the form of differential equations from the solutions of which it follows that the transient process in the tribosystem is described by second-order vibrational links. It is established that the nature of the transient process after application to the tribosystem of the input action depends on the gain factors and time constants, as well as the damping decrement values. Experimental evaluation of the adequacy of simulation results to experimental data was carried out. The values of the simulation error are obtained when the main factors affecting the transient process are changed: the tribological properties of the lubricating medium; rheological properties of the structure of conjugate materials; form factor; surface roughness; load and slip speed. It was found that the maximum error in modeling the wear rate does not exceed the values eI = 11.9 ... 16.6 %, and the coefficient of friction ef = 13.0 ... 18.5 %. In this case, the maximum error value corresponds to the surface roughness factor.